Microbial community of cultivated and uncultivated citrus rhizosphere microbiota in Brazil - Helena Santiago Lima; Nathália Mancine; Giovana Betin Peruchi; Carolina Sardinha Francisco; Nian Wang; Rafael Soares Correa de Souza; Jaderson Silveira Leite Armanhi; Helvecio Della Coletta-Filho (Scientific Data)
Abstract The rhizosphere microbiome is known to contain beneficial microorganisms that promote plant growth and increase tolerance to abiotic and biotic stresses. Understanding citrus microbiome diversity and the percentage of diversity that can be recovered in the laboratory is essential for developing innovative approaches to improve plant health and promote sustainable agricultural practices. However, information about the citrus root microbiome, especially in the context of exploring commercial citrus growing areas to identify beneficial plant growth-promoting rhizobacteria (PGPR), is scarce. Here, we present the microbiome data of healthy citrus trees sampled from geographical regions of São Paulo and Amazonas States, in Brazil. The resulting rhizosphere microbiome data comprise an average of 126,180 and 138,707 high-quality reads for the 16S rRNA V3–V4 and ITS1-5F regions, respectively. The taxonomic analysis of cultivated diversity revealed a total of 91 bacterial genera recovered in the laboratory. These data provide valuable information for understanding how the microbiome supports citrus plants in different environments and for developing new strategies to improve crop productivity by using PGPR.